GENETIC AND ENVIRONMENTAL RISK FACTORS OF INCIDENT DIABETES FROM THE MULTIETHNIC COHORT STUDY. (16th November 2018) - Youkhana, F; Pirkle, C; Thompson, M; Wilkens, L; Le Marchand, L; Cheng, I; Wu, Y
Abstract: While genetic predisposition can increase the risk of diabetes, both genetic and environmental factors interact across the life-course to influence disease risk. Few studies examine both factors simultaneously. Genome-wide association studies (GWAS) consistently observe associations between the CDKAL1 gene and diabetes, but GWAS on ethnic minority populations is rare. Using the Multiethnic Cohort (MEC), GWAS was conducted on a sample of 5211 Blacks, Latinos, Japanese, Native Hawaiians, and Whites from Hawaii and Los Angeles, who were 44 years and older at baseline (1993–1996). Since, incident doctor-diagnosed diabetes was recorded and rs10440833 in CDKAL1 was replicated as a risk factor for diabetes in MEC. Stratified by race/ethnicity, we next conducted Poisson regressions with robust error variances to examine the risk of incident diabetes considering life-course and social risk factors—age, sex, family size, number of children, place of birth, marital status, education—health behaviors—smoking, alcohol consumption, diet, exercise, and sleep—and rs10440833. Accounting for the environmental factors, rs10440833 was only a significant risk factor for diabetes among Japanese participants (RR: 1.21, 95%CI: 1.06–1.37). The only variable consistently associated with increased risk of incident diabetes across all racial/ethnic groups was increasing age (RR varied from 1.02 for blacks to 1.06 in whites). Health behaviors were only statistically significant for Japanese (smoking, diet and alcohol) and Native Hawaiians (sleep and physical activity). Our analyses suggest race/ethnicity specific risk factors for incident diabetes in this older sample and highlight the importance of including a wider variety of ethnic groups in GWAS.